POSITIONING OF THE STATE AS ONE OF THE METHODS TO INCREASE THE INVESTMENT ATTRACTIVENESS IN SOUTH OSSETIA - Dzambolat M. Tadtaev; Yury I. Zhevora; Vladimir N. Ryabov (Вестник Северо-Кавказского федерального университета)
The item offers a view on the main issues regarding the investment attractiveness in term of positioning the Republic of South Ossetia. The authors offer a conceptual approach to positioning the Republic of South Ossetia following the target points. There are also factors for investment development identified.